Antiplatelet mechanism of an herbal mixture prepared from the extracts of Phyllostachys pubescens leaves and Prunus mume fruits - Eunjung Son; Seung-Hyung Kim; Won-Kyung Yang; Dong-Seon Kim; Jimin Cha (BMC, 2017)
Abstract Background Bamboo (Phyllostachys pubescens) leaves and Japanese apricot (Mume fructus) fruit are traditionally recognized to be safe herbs broadly used for food and medicinal purposes in Southeast Asia. Our group previously explored their antiplatelet effects. This study was designed to confirm inhibition effects of PM21 (a 2:1 mixture of bamboo leaf extract and Japanese apricot fruit extract) on platelet aggregation and evaluate its potency to use as an herbal remedy to prevent and/or treat the diseases caused by platelet aggregation and thrombus formation. Methods Washed platelets were prepared and platelet aggregation was induced by adding 5 μg/mL collagen. Anti-platelet effects of PM21 (75 mg/kg, 150 mg/kg, and 300 mg/kg for ex vivo and in vivo assays, and 50, 100, 200 μg/mL for in vitro assays) were evaluated. In ex vivo assays, PM21 was orally administered to rats daily after overnight fasting for 3 days and blood was collected 1 h after the final treatment. In vivo antithrombotic effect of PM21 was observed from a carrageenan induced mouse tail thrombosis model. Results In ex vivo assay, PM21 inhibited platelet aggregation significantly. PM21 showed a strong antithrombotic effect by reducing significantly the length of mouse tail thrombus. PM21 increased intracellular cAMP level and reduced the release of ATP, TXA2, and serotonin. PM21 also reduced intracellular concentration of calcium ion, fibrinogen binding to integrin αIIbβ3, and phosphorylation of ERK2, p38, PLCγ2, and PI3 K. Conclusions PM21 showed remarkable inhibitory effects on platelet aggregation and thrombus formation. Its inhibitory function seems to influence on GPVI binding to its ligand and subsequent initiation of a signaling cascade that involves activation of effector proteins and secretion of effector molecules, such as ATP, TXA2, serotonin, and Ca2+. PM21 also appears to exert its anti-platelet effect by deactivation of ERKs activation pathway as well as inhibition of fibrinogen binding to integrin αIIbβ3.